(untitled) (Global Journal of Science Frontier Research, 2015)
For a better understanding toward corrosion in metallic electrode of copper and aluminum. Such factors with an influence on the corrosion were investigated via the hydrogen production process by electrolysis of water. The phenomenon of electrode corrosion was studied, and the corrosion is resulted in the appearance of large blisters and a gelatinous alumina gel Al (OH) 3 . In addition, the measurements tests of reaction mid, used time, deposit, temperature of electrolyte and degree of pH on the metal corrosion regions were also conducted. According to the test results, the corrosion was strongly affected by these factors. Furthermore, the corrosion was necessarily depends on the medium pH value, an increase in temperature greatly increased the corrosion rate and the surface can be covered with a deposit of corrosion products (metal oxide hydrated, insoluble salts). The role of this film can influenced the corrosion was worsening the attack.